MENILIK ULANG PERADABAN ISLAM Sebuah Kajian Nas danSejarah - Taufiqurrahman Kurniawan (Program Studi Hukum Keluarga Islam, 2017)
The history of the Arabs of the past has followed the teachings of Ismail As and Ibrahim As. The doctrine that contains worship, crowding only to Allah SWT. But it has been marred by his followers named 'Amr bin Luhay a leader of Banu Khuza'ah by adding to the teachings of Abraham. Along the course of history, there was an Islamic civilization, but many historians wrote when the historic event took place. Many kinds of opinions in determining the month of the fall of revelation is the month of early Rabiul. There is also a set month of Ramadan. Another class sets the first revelation in Rajab by conveying all sorts of arguments. There is an opinion about the date at which the revelation was revealed to the Prophet (s). Some opinions specify the seventh date, there are also on the seventeenth, there are opinions on the eighteenth, other opinions of the nineteenth and there are also opinions that set the date of twenty-one. But historians agreed on Monday when revelation was revealed to Prophet Muhammad SAW. The question is when will the first revelation be revealed and how is the method used to extract the truth? The basic approach used is with the approach bayani and burhani. Ie used historical data or history (verse, hadith and tarikh) which is data serve and astronomical data which is data burhani. The analysis is done by cross-confirmation between data bayani and burhani data. Having processed these data then found conclusion that data burhani (astronomy) in accordance with the data bayani (history or history) stating that Badr War happened on 19th of Ramadan and thus al-Quran revealed the first time that marked the birth of Islamic civilization is on the day Monday 19th Ramadan year 14 SH coincides with August 25, 609 M. So the age of Islamic civilization on Tuesday, 18th Ramadan 1438 H just last, even reached the age of 1451 years kamariah and Wednesday, 19th Ramadan 1438 H is his birthday- 1451.